Eksistensi Partai Golkar di Kabupaten Labuhanbatu pada Pemilu 2009 - HUSNUL ISA HARAHAP (Universitas Sumatera Utara, 2011)
that time this party is the winner party. Nevertheless situation has changed after political reform in 1998. Since this era, Golkar Party must full tactical for win the competition. This Study is discussing change of Golkar Party vote at general election 2009. Precisely, present which piece of vote the Golkar Party which obtained at general election 2004 that change at 2009. This study is using observation way, interview and book study and document for collect-ing data. Data Analysis is using comparison method (the vote) combine with political behavior approach. The finding is the reduction of Golkar Party vote in Labuhanbatu influenced by his popular figure (got voter) that has decreased. It is affect to all of constituency at this place. Though this party is winner at Dapil Labuhanbatu 1 dan 5, but the degradation of Golkar Party vote is inescapable. This condition indicates the electors that select Golkar Party (2004) and then not (2009) in general election, is categorized as voter candidate orientation.Keywords: General election, political party, political participation.